Why change the name of the College from Australasian to Australian and New Zealand?. (31st October 2017) - Ardagh, Michael
Abstract: Australasian is the adjectival version of the name of a geographical region. The region is defined differently by different people. It includes islands other than Australia and New Zealand and variably includes or excludes New Guinea. It has nothing to do with Asia. The adjective is often misunderstood, it leaves New Zealand invisible to many readers and it is an incorrect description of who we are as a college. Australian and New Zealand describes who we are – fellows from two sovereign nations – Australia and New Zealand. Changing the name is not about secession, division nor ingratitude and does not undermine the College's commitment to helping other nations in the greater region. It is a positive acknowledgement of who we are and a strong foundation for a united College's future growth.